Calvary Methodist Church on 19th Avenue and Judah Street - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait beside Calvary Methodist Church on the corner of 19th Avenue and Judah Street in San Francisco, California. The nature of this gathering and the relation it has to Calvary Methodist Church is unknown.